Penyidikan oleh Kejaksaan Terhadap Tindak Pidana Korupsi yang Dilakukan Aparat Penegak Hukum - Ainus Sofa Ilmi; Dwi Endah Nurhayati; Halif Halif; Echwan Iriyanto; Dodik Prihatin AN (UNES Law Review, 2023)
Based on Article 11 paragraph 1 of the Corruption Eradication Commission Law, the investigation process for criminal acts of corruption falls under the authority of the KPK. However, most of these investigations are carried out by the police or prosecutors. So whether prosecutor investigators have the authority to investigate corruption crimes against law enforcement officials is reviewed based on the Prosecutor's Law in conjunction with the Corruption Eradication Commission Law. As well as what are the legal consequences of investigations conducted by prosecutor investigators against law enforcement officials who commit acts of corruption in terms of the Corruption Eradication Commission Law. The results of this study can be concluded first, that the prosecutor's office has the authority to investigate criminal acts of corruption committed by law enforcement officials. However, based on the principle of lex specialis derogat legi generalis, it is the KPK that is in charge. Second, based on the provisions of the KPK Law, the KPK can take over the investigation process. This takeover attempt was not carried out by the KPK so that the KPK violated the code of ethics because it did not carry out its duties and authorities properly.